Вплив інноваційно-кластерного розвитку на конкурентоспроможність регіонів і країни - Міщенко, Володимир Акимович; Авершин, Сергій Володимирович (Jagiellonian University, Poland, 2021)
A quantitative assessment of innovation and cluster development using various international indices and rankings conducted by well-known world agencies. The advantages and disadvantages of the development of national clustering from the international level are revealed. The presence of a correlation between the main indicators of competitiveness is determined. The main internal problems of clustering development are described in the National Cluster Development Program until 2027 and directions for improving this process in the future. Addressing these issues requires improving the efficiency of management at all levels.

Проведена кількісна оцінка інноваційно-кластерного розвитку з використанням різних міжнародних індексів та рейтингів, які проводяться відомими світовими агенствами. Виявлені переваги й недоліки розвитку національної кластеризації з міжнародного рівня. Визначено наявність кореляційної залежності між основними показниками конкурентоспроможності. Описані основні внутрішні проблеми розвитку кластеризації в Національній програмі кластерного розвитку до 2027 року і напрями вдосконалення цього процесу в майбутньому. Рішення цих питань потребує підвищення ефективності менеджменту на всіх рівнях
The Influence of Innovation and Cluster Development on the Competitiveness of Regions and Countries
Keywords: cluster; competitiveness; strategy; innovation; program; development; indicator; index; share; factor; кластери; конкурентоспроможність; стратегія; інновації; програми; розвиток; показники; індекси; питома вага; фактори